Family Embeddedness and Medical Students’ Interest for Entrepreneurship as an Alternative Career Choice: Evidence From China - Zhao, W. G. Will; Liu, Xiaotong; Zhang, Hui (Frontiers in Psychology, 2021)
Joining the ongoing academic debates around medical students’ alternative career choices, this research examines the role of family in medical school attendees’ entrepreneurial intention (EI). Specifically, this study decomposes the multi-dimensionality of family embeddedness and highlights the mediated nature of the family-EI relationship. The empirical analysis relied on data from graduation year medical students from diverse geographical locations and from different institution types in China. These data were collected from a total of 687 questionnaires covering the basic information of individual, parents, and family composition, as well as the measuring scale of EI. Examining medical students’ EI and its antecedents provide a dual-missing-link in the extant knowledge, i.e., it adds the medical school piece to the overall picture of university students’ EI, and equally important, it de-trivializes entrepreneurship from the extant theorizations of medical students’ career choices. This study also bears implications for educators, practitioners, and policymakers interested in better understanding EI of medical school attendees and family embeddedness.